Erythrocyte sodium/lithium countertransport is associated with thrombotic and fibrinolytic factors in 58-year-old men - Herlitz, Hans; Bokemark, Lena; Fagerberg, Björn (Thrombosis and Haemostasis, 2004)
The metabolic syndrome, in which insulin resistance is the core feature, is associated both with dysregulation of thrombosis/ fibrinolysis and erythrocyte sodium/lithium countertransport (SLC).To investigate this further we designed a cross-sectional study to examine whether factors involved in coagulationand fibrinolysis systems were associated with SLC independently of insulin resistance in 93 58-year-old men. SLC was in univariate analysis positively correlated with PAI-1 activity (r = 0.35, p <0.01), tPA antigen (r = 0.38, p <0.01), von Willebrand factor (r = 0.25, p <0.05), protein S (r = 0.26, p <0.05), and C (r = 0.30, p <0.01), and negatively associated with tPA activity(r = −0.28, p <0.01). Since these correlations could be influenced by the components of the metabolic syndrome itself, a separate analysis with adjustment for glucose infusion rate (GIR), plasma insulin, body fat, sagittal diameter of the abdomen (SD) and log serum triglyceride concentration (TG) was conducted. Then SLC was associated with tPA antigen independent of GIR, plasma insulin, body fat, SD and TG. SLC was also associated with protein C independent of GIR, insulin, body fat and SD but not TG. In conclusion, we found a relationship between SLC and the fibrinolytic system that was not related to the metabolic syndrome.
Keywords: Sodium/lithium countertransport; fibrinolysis; coagulation; metabolic syndrome; renin-angiotensin system